OC-024 Detect inspect characterise resect and discard 2: are we ready to dispense with histology?. (22nd June 2015) - Rajasekhar, PT; Mason, J; Wilson, A; Close, H; Rutter, M; Saunders, B; East, J; Maier, R; Moorghen, M; Rees, C
Abstract : Introduction: Colorectal cancer is preventable through polypectomy at colonoscopy. Most polyps are adenomas, with malignant potential, or hyperplastic with no malignant risk. Most adenomas are small (<10 mm) with minimal chance of harbouring cancer. Accurate optical diagnosis during colonoscopy would allow small adenomas to be removed and discarded and rectosigmoid hyperplastic polyps to be left in-situ. Narrow band imaging (NBI) in expert hands allows accurate optical diagnosis and assignment of surveillance intervals. Method: The accuracy of surveillance interval assigned by NBI optical diagnosis was compared with the current reference standard of histopathological diagnosis in a prospective, blinded calibration study in 6 community hospitals in northeast England. Adults undergoing routine colonoscopy between July 2012 and February 2014 were eligible. Exclusion criteria were: inflammatory bowel disease; polyposis syndromes; pregnancy. Participating colonoscopists (n = 28) passed a validated training module utilising the NBI International Colorectal Endoscopic (NICE) classification. Optical diagnosis was provided for all polyps <10 mm and surveillance interval when only small polyps were present. Results: Of 1688 patients recruited, 723 (42.8%) had polyps <10 mm of which 567 (78.4%) only had polyps <10 mm. The sensitivity, specificity and negative predictive value of optical diagnosis (n = 499 patients) in determining the need for colonoscopic surveillance were 73.0% (95% CI: 66.9–79.9%), 75.6% (95% CI: 70.9–80.1%) and 85.2% (95% CI: 81.0–89.1%). The sensitivity and specificity per polyp (n = 1620 polyps) was 76.1% and 77.5%. If ≥ 2 NICE features were identified, then sensitivity was 95–100%. Conclusion: The findings of this study suggest that NBI optical diagnosis cannot yet be recommended for use in routine clinical practice. Sensitivity per polyp was acceptable when ≥2 NICE features were present. Further work is required to determine if variation is due to colonoscopist or polyp characteristics. Disclosure of interest: None Declared.